Kvinnotidningar: Idun - Språkbanken Text (University of Gothenburg, 2024)
A corpus with texts from the women's newspaper Idun

En korpus med texter från kvinnotidningen Idun, praktisk veckotidning för kvinnan och hemmet
Kvinnotidningar: Idun
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik